2000
DOI: 10.1002/1096-9071(200010)62:2<185::aid-jmv9>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interferon treatment on serum 2?,5?-oligoadenylate synthetase levels in hepatitis C-infected patients

Abstract: Interferon (IFN) is widely used for patients with hepatitis C. Less than half of treated patients respond to IFN therapy, however, and increased resistance to IFN is particularly observed in genotype 1b patients. Recently, genotype 1b patients with the wild type sequence in the NS5A gene were shown to be resistant to therapy, suggesting that the NS5A protein may be involved to IFN resistance. Thus, we investigated the serum 2',5'-oligoadenylate synthetase (2',5'-OAS) levels before and during IFN treatment. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
1
12
2
Order By: Relevance
“…Other studies in HCV-infected patients have shown that interferon-based therapy is associated with upregulation of OAS and ISG15, although this does not necessarily predict long-term outcomes. [26][27][28][29] In this study, we did not observe substantive increases in these markers after a single dose of isatoribine; however, dose-related increases in expression of both OAS (Fig. 3) and ISG15 Fig.…”
Section: Resultscontrasting
confidence: 65%
“…Other studies in HCV-infected patients have shown that interferon-based therapy is associated with upregulation of OAS and ISG15, although this does not necessarily predict long-term outcomes. [26][27][28][29] In this study, we did not observe substantive increases in these markers after a single dose of isatoribine; however, dose-related increases in expression of both OAS (Fig. 3) and ISG15 Fig.…”
Section: Resultscontrasting
confidence: 65%
“…Its antiviral effects are initiated by synthesis of 2Ј,5Ј-oligoadenylates that activate an endoribonuclease to cleave double-stranded viral RNA. 2Ј,5Ј-OAS is considered to be a reliable biomarker of IFN-␣ exposure, although its relationship to long-term clinical response is not clear (Moritz et al, 1992;Fischer et al, 1996;Murashima et al, 2000). 2Ј,5Ј-OAS mRNA levels were significantly higher after a single Albuferon injection than after three 40 g/kg IFN-␣ injections every other day, and the duration of effect was also longer (up to 10 days).…”
Section: Discussionmentioning
confidence: 99%
“…HCV cell-based expression models show inhibition of IFN-␣-induced signal transduction through the Jak/STAT pathway (22,26,55,76). Among all ISGs, the best characterized effector proteins are the double-stranded RNA-activated protein kinase (PKR) (41), the 2Ј,5Ј-oligoadenylate synthetase (92), and the Mx proteins (134). Besides its antiviral activities, IFN-␣ also affects processes that regulate cell growth and the modulation of the immune response.…”
Section: Ifn-␣ Signal Transductionmentioning
confidence: 99%